Welcome to the neighborhood - Roe, Lisa (Sourcebooks Casablanca, 2022)
"What lengths will a mother go to protect what's most important? Ginny Miller's re-marriage is a great opportunity to move with her quirky eleven year-old daughter to an upscale New Jersey suburb-but reality in the Real Housewives of NJ town isn't everything she hoped it would be"--